2022
DOI: 10.1002/slct.202103848
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, In‐Vitro Evaluation and Molecular Docking Study of N‐Substituted Thiazolidinediones as α‐Glucosidase Inhibitors

Abstract: Thiazolidinedione (TZD) drugs have been shown to improve insulin sensitivity, hyperglycemia, and lipid metabolism in people with type 2 diabetes mellitus. In this study, we have explored the alpha‐glucosidase inhibitor action of new N‐substituted 5‐benzylidene‐2,4‐thiazolidinedione derivatives. Various substituted benzothiazoles linked to the 5‐benzylidene‐2,4‐TZD with acetamide linker were synthesized and characterized by FTIR, 1H‐NMR, 13C‐NMR, and mass spectrometry. After the in‐silico screening of all the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…When compared to acarbose (IC 50 = 67.06 ± 1.24 μM), most compounds displayed extremely considerable inhibitory activity towards α-glucosidase. 46 Flavonoids are known to play a function in hypoglycemia via blocking α-glucosidase. A study indicated that the diverse flavonoid compounds exhibited inhibitory activity and good docking score and the presence of Asp 215 was implicated in the hydrogen-bonding interaction between each flavonoid with the enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…When compared to acarbose (IC 50 = 67.06 ± 1.24 μM), most compounds displayed extremely considerable inhibitory activity towards α-glucosidase. 46 Flavonoids are known to play a function in hypoglycemia via blocking α-glucosidase. A study indicated that the diverse flavonoid compounds exhibited inhibitory activity and good docking score and the presence of Asp 215 was implicated in the hydrogen-bonding interaction between each flavonoid with the enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesized N‐Substituted Thiazolidinediones, In‐Vitro study and Molecular Docking Study, and α‐Glucosidase Inhibitory activity of N‐Substituted Thiazolidinediones. Compound 46 has showed promising inhibitory α‐glucosidase activity with IC 50 : 29.91±0.82 μM and molecular docking study suggests the formation of three hydrogen bonds with Asp232, Ser497, and Ser505 [54] . RB C et al.…”
Section: Discussionmentioning
confidence: 99%
“…[53] Patil Ser497, and Ser505. [54] RB C et al identified rhodanine benzothiazole compounds as α-amylase and α-glucosidase inhibitors. Compound 47 showed good activity with IC 50 : 24.22 � 1.65 μM and IC 50 : 28.4 � 0.57 μM as compared to standard acarbose and We found Asp1279 and Hie1584, respectively, in hydrogen bonding interactions including hydroxyl and methoxy group substitution on the phenyl ring.…”
Section: Pharmacological Characteristics Of Benzothiazole Analoguesmentioning
confidence: 99%
“…The docking simulation was performed using Molecular Operating Environmental (MOE) 10.2009 soware 53,54 inside the active site of a-amylase (PDB: 2QV4), a-glucosidase (PDB: 3w37), and PPAR-g (PDB: 3SZ1). [55][56][57] 2.4.1. Ligand-protein complex interaction inside aamylase (PDB: 2QV4).…”
Section: In Silico Molecular Docking Simulationmentioning
confidence: 99%
“…To determine the binding mode pattern for the most active chromene derivatives 2 and 9, the docking simulation conducted inside the active site of a-amylase (PDB: 2QV4, chain A), a-glucosidase (PDB: 3w37, chain A), and PPAR-g (PDB: 3SZ1, chain B) as described previously. [55][56][57] The 3D structure of proteins was obtained from the protein data bank (https:// www.rcsb.org/), and each protein was prepared by default protocol where the water molecules were removed, and only one chain was selected for docking purposes. The active site was protonated, then the energy was minimized using MMFF94X with a gradient of 0.05 kcal mol −1 and saved as an mdb le.…”
Section: Molecular Docking Simulationmentioning
confidence: 99%